Vascular Pythiosis of the Lower Extremity in Northern Thailand: Ten Years Experience - Termpong Reanpang (2018)
© SAGE Publications. Pythiosis is a disease caused by Pythium insidiosum, a fungus-like organism. P. insidiosum is pathogenic in mammals, particularly in horses, dogs, and humans. Human pythiosis can be classified into 4 types: (1) cutaneous/subcutaneous, (2) ocular, (3) vascular, and (4) disseminated pythiosis. Vascular pythiosis is a rare disease but a serious limb- and life-threatening infection. We reviewed 22 cases over a 10-year period in Maharaj Nakorn Chiang Mai/Chiang Mai University Hospital. The survival rate was around 63.6% during our follow-up period. The only effective treatment was complete excision of the infected tissue, which was done mainly by major amputation, such as above-knee amputation. This report raises awareness of this disease, which needs preemptive diagnosis and appropriate treatment.